Do peer-based education interventions effectively improve vaccination acceptance? a systematic review - Elisa L. S. Gobbo; Claudia Hanson; Khadija S. S. Abunnaja; Sibylle Herzig van Wees (BMC, 2023)
Abstract Background Vaccination efforts are a vital part of controlling the spread of diseases, however, lack of vaccine acceptance undermines the efficacy of this public health effort. Current evidence suggests that the most effective interventions to support vaccination uptake and positive vaccination beliefs are multicomponent, and dialogue based. Peer-based education interventions are such a strategy that involves an individual within the same group to act as the vaccine educator. Objective This review aims to consolidate the quantitative evidence surrounding the effectiveness and experience of peer-based education initiatives to improve vaccination beliefs and behaviors. Methods We conducted a systematic search of PubMed, Web of Science, and a hand reference search. The search was conducted between April and June 2022. The inclusion criteria encompassed using peers, being education based, and being an intervention that addresses vaccination beliefs and behaviors (e.g. vaccination uptake). Results Systematic screening revealed 16 articles in the final review. Half of the studies focused on students as their study population. The human papillomavirus vaccine was the most common vaccine assessed in the studies, followed by COVID and influenza vaccines. 11 out of 16 of the articles reported a positive impact of the peer intervention and two studies had mixed results. Six studies suggest a mixed peer- healthcare expert approach. Conclusions Despite reported positive effects of using peer-education based initiatives to improve vaccine uptake and beliefs, this systematic review reveals that there is limited existing research in support of this strategy. The strategies that initially appear the most effect are those with a combined peer and health-expert approach, and those that have more group specific and long-term peer interventions. More research is needed to confirm these results and to assess the effectiveness of a peer-based education intervention in a wider variety of settings and for other vaccine types.